Institutional factors affecting fish passage in the Columbia River Treaty renegotiation. Issue 7 (3rd October 2018) - Lee Rowlands, Graeme A.; Wildman, Richard A.
ABSTRACT: The United States and Canada have begun renegotiating the Columbia River Treaty, which is an international model for transboundary water governance. This paper identifies six institutional factors that will affect negotiations pertaining to fish passage during the renegotiation of the treaty: geographical advantage, issue linkage, a basin commission, the duration of agreements, negotiating autonomy and side payments. These factors and the methods used to determine them can be applied to other transboundary river basins where basin states have a history of transboundary resource governance. This analysis also serves as a policy-relevant resource for Columbia River Treaty negotiators and stakeholders.